THE EFFECTIVENESS OF REASONING-GAP ACTIVITY TO IMPROVE THE STUDENT’S ARGUMENT WRITING - Geraldine, Monitha (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research attempted to find out whether teaching writing arguments in discussion text through reasoning-gap activity based on Task-Based Language Teaching (TBLT) was effective or not. To accomplish the purpose of this study, quasi experimental design was utilized. The measurement technique was employed in this research. The data collection instrument was written test. T-test formula was applied to analyze the quantitative data obtained through written test, while an analytic scoring rubric was developed to assess the students? argument writing in discussion text. The results of data analysis through statistical procedure of t-test confirmed the superiority of the experimental group to the control group, and reasoning-gap activity helped the students to improve writing argument in discussion text. Keywords: Reasoning-Gap Activity, TBLT, Argument Writing, Discussion Text